Carbon stocks of an Oxisol after thirty-eight years under different tillage systems - Sulamirtes S. de A. Magalhaes; Fabricio T. Ramos; Oscarlina L. dos S. Weber (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Soil carbon (C) stock determination can subsidize discussions on the continuity of an agricultural management. This study aimed to evaluate the stocks of total organic C (STOC) and labile C (SLC), and the indices of C lability (CLI), C compartment (CCI) and C management (CMI), and correlate them with chemical and physical attributes of a Red Yellow Latosol (Oxisol) managed for 38 years with different tillage systems in a Cerrado region of Mato Grosso, Brazil. Disturbed and undisturbed soil samples were collected in three layers (0-0.05, 0.05-0.10 and 0.10-0.20 m). The CMI (CLI x CCI) showed higher STOC possibly as the tillage depth decreased, because none of the tillage systems conserved STOC and SLC in the layers of 0-0.05 and 0.05-0.10 m, compared with the Native Cerrado, i.e., soil C conservation only occurred in the layer of 0.10-0.20 m. Although the percentage of SLC in STOC was lower, only SLC was correlated with soil chemical and physical attributes and, based on the multiple linear regression analysis, SLC was explained in 54% (R2) by the cation exchange capacity and soil micropores. Therefore, for monitoring purposes, the SLCestimated can be useful to evaluate soil C storage.